ANTIMICROBIAL ACTIVITY OF ORGANIC LEAF EXTRACT OF SESBANIA SESBAN AGAINST GRAM NEGATIVE PATHOGENIC BACTERIA : Pharmaceutical Science-Biotechnology - NIROSHA, MUKKALI; PAVANI, KANKANALA; KOMALA PRIYA, ARUNACHALAM; HASEENA, URIMILLA; JYOTHSNA, SANGEETHAM (International Journal of Life Science and Pharma Research, 2019)
Sesbania sesban, belonging to family Leguminosae, is a well-recognized medicinal plant. It is widely distributed in our country. Sesbania sesban is an erect, branched small tree up to 6 m tall with soft wood and paripinnate leaves. Flowers are yellow with brown streaks on the corolla. Fruits are sub cylindrical and shortly beaked. Seeds are green or brown and usually mottled. The plant is used as carminative, antihelmintic, astringent, anti-inflammatory, antimicrobial, antifertility, demulcent and purgative. It is also given as a medicine against fever andulcers. The medicinal value of plants depends up on the chemical compounds that produce in in the human body during a specific reaction. chemical substances responsible for such reactions are called secondary metabolites. The most important of these bioactive compounds are alkaloids, terpenoids, steroids, flavonoids, tannins and phenolic compounds. By keeping these properties of bioactive compounds of Sesbania sesban in view the present investigation was undertaken to screen phytochemical constituents. Preliminary phytochemical screening of leaf in three different extracts (ethanol, methanol and aqueous extract) revealed the presence of carbohydrates, tannins, saponins, glycosides, steroids, flavonoids, phenols, terpenoids, alkaloids and glycosides which indicated antimicrobial activity of the Sesbania sesban leaves. The other objective was to investigate antimicrobial activity of three solvent extracts against gram negative pathogenic bacteria viz, Escherichia coli, Pseudomonas aeruginosa and Klebsiella pneumoniae. Among the three extracts, ethanol showed the maximum activity. Zone of inhibition caused by ethanol against Escherichia coli, Pseudomonas aeruginosa and Klebsiella pneumoniae at (50µl, 100µl, 150µl) is 25%, 24.5% and 18.8% higher, respectively than caused by methanol and aqueous extracts of Sesbania leaves. Ethanol extract of Sesbanialeaves potentially act as antimicrobial agent